Circ_0008305‐mediated miR‐660/BAG5 axis contributes to hepatocellular carcinoma tumorigenesis. (22nd January 2021) - Yan, Fuguo; Fan, Bin; Wang, Jianchu; Wei, Wang; Tang, Qianli; Lu, Libai; Luo, Zongjiang; Pu, Jian; Yang, Shan‐Shan
Abstract: Increasing circRNAs have attracted a lot of attention because of their significant biological effects in many diseases. It has been reported that circ_0008305 can modulate lung cancer progression. However, the association between circ_0008305 and hepatocellular carcinoma (HCC) needs to be well explored. In this current research, we studied the molecular function and potential mechanism of circ_0008305 in HCC progression. First, it was demonstrated that circ_0008305 was greatly increased in HCC tissues and cells. Moreover, we observed silencing circ_0008305 markedly repressed HCC cells in vitro growth and reduced tumor growth in vivo. Additionally, it was identified that circ_0008305 can act as a sponge of miR‐660 while miR‐660 targeted Bcl‐2‐associated athanogene 5 (BAG5). BAG5 belongs to a member of BAG family and it is involved in multiple diseases. We reported that circ_0008305 contributed to the inhibition of miR‐660, which resulted in an upregulated expression of BAG5 in HCC. Subsequently, rescue assays were conducted and it was indicated that loss of BAG5 reversed the effects of miR‐660 inhibitors on HCC partially. To sum up, it was illustrated by our study that circ_0008305‐mediated miR‐660‐5p/BAG5 axis triggered HCC progression, which could provide a novel insight on the underlying mechanism of HCC progression. Abstract : circ_0008305 was greatly increased in HCC tissues and cells. circ_0008305 can act as a sponge of miR‐660. miR‐660 targeted Bcl‐2‐associated athanogene 5 (BAG5).